Level of Mycobacteria in Pre-treatment Sputum and Susceptibility of M. Tuberculosis Strains Isolated from Patients with Non-multidrug-resistant Pulmonary Tuberculosis AFB (+) and Factors Influencing MGIT Results after the First 8 Weeks of Anti-tuberculosi - Dong, Pham Dinh; Cuong, Nguyen Kim; Thi Phuong, Nguyen; Ngoc Hong, Nguyen; Van Hung, Nguyen; Son Nhat, Bui; Thi Luyen, Le (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2021)
This study assesses the level of mycobacteria in sputum before treatment, and susceptibility of M. Tuberculosis strains isolated from TB patients with AFB (+) and non-multidrug-resistance to the first-line anti-TB drugs. Factors influencing MGIT outcome after the first 8 weeks of first-line anti-TB drugs therapy in patients with pulmonary tuberculosis were also analyzed. The study performed an analytical observation of 128 patients with non-multidrug-resistance pulmonary tuberculosis AFB (+) for evaluating the level of Mycobacteria in sputum before treatment by smear microscopy method; the susceptibility of M. tuberculosis isolated from sputum of the patient was analyzed by Lowenstein - Jensen method. Factors affecting positive MGIT results after 2 months of treatment were determined by multivariate logistics regression. The study results show that the patients having AFB3+ accounted for 28% of the new cases and 24.5% of the retreatment patients. The percentage of any anti-TB drug resistance in the retreatment tuberculosis was 59.6%, higher than that of the new case TB (23.6%). There was a high rate of M. tuberculosis strains resistant to Streptomycin and Isoniazid (12.5% and 16.8% for the new cases; 42.3% and 36.5% for the retreatment cases, respectively). Large radiographic chest lesions and high AFB levels in pre-treatment sputum were factors associated with a positive MGIT result after the first 8 weeks of treatment. Most of the TB patients had a high level of mycobacteria in sputum samples collected before treatment. The percentage of M. tuberculosis strains isolated from sputum of pulmonary non MDR-TB patients with any anti-TB drug resistance was high. High mycobacteria level in pre-treatment sputum and radiographic chest lesions related to positive MGIT result after the first 8 weeks of treatment. Keywords Pulmonary tuberculosis, first-line anti-TB drugs, anti-TB drug resistance, susceptibility, M. tuberculosis . References [1] World Health Organization, Global Tuberculosis Report 2020. Tuberculosis profiles: Viet Nam (2020) Available: https://worldhealthorg.shinyapps.io/tb_profiles/?_inputs_&entity_type=%22country%22&lan=%22EN%22&iso2=%22VN%22 (accessed 10 April 2020). [2] L.T. Luyen, N.V. Hung, Methods for Diagnosis in Tuberculosis, in Le Thi Luyen (Ed), Tuberculosis - Textbook for General Medical Students. Vietnam National University Press, Hanoi, 2020, pp: 47-69 (in Vietnamese). [3] Ministry of Health - National Tuberculosis Programme Guideline for Standard Operating Procedures of Microbiology Laboratory Methods for Mycobacteria. Vietnam National Tuberculosis Programme, Hanoi (2013) (in Vietnamese). [4] Ministry of Health (2018) Guideline for Management, Diagnosis and Treatment for Tuberculosis. (in Vietnamese) Available: https://kcb.vn/vanban/quyet-dinh-so-3216-qd-byt-ngay-23-5-2018-ve-viec-ban-hanh-huong-dan-chan-doan-dieu-tri-va-du-phong-benh-lao (Accessed 12 January 2019) [5] A.P. Ralph, M. Ardian, A. Wiguna et al. A simple, valid, numerical score for grading chest x-ray severity in adult smear-positive pulmonary tuberculosis. Thorax 2010 Oct;65(10):863-869. https://doi.org/10.1136/thx.2010.136242 [6] C.T. Minh, L.T. Luyen, N.T.L. Huong et al. Plasma concentration of anti-tubeculosis drugs in pulmonary tuberculosis patients, who treatment in National Tuberculosis and Lung Diseases Hospital 2008 Journal of Practical Medicine 651(2009) 50-53 (in Vietnamese). [7] N.V. Nhung, N.B. Hoa, D.N. Sy, C.M. Hennig, A.S. Dean (2015) The fourth national anti-tuberculosis drug resistance survey in Viet Nam. Int J Tuberc Lung Dis. Jun 2015 19(6) 670-675. https://doi.org/10.5588/ijtld.14.0785 [8] N.T. Hang, S. Maeda, L.T. Lien, et al. Primary drug-resistant tuberculosis in Hanoi, Viet Nam: present status and risk factors. PloS one 8(8) (2013) e71867. https://doi.org/10.1371/journal.pone.0071867 [9] R. Hafner, J.A. Cohn, D.J. Wright, et al. Early bactericidal activity of isoniazid in pulmonary tuberculosis. Optimization of methodology. The DATRI 008 Study Group. Am J Respir Crit Care Med 156 (1997) 918–923. https://doi.org/10.1164/ajrccm.156.3.9612016 [10] A. Jindani, V.R. Aber, E.A. Edwards, D.A. Mitchison. The early bactericidal activity of drugs in patients with pulmonary tuberculosis. Am J Respir Crit Care Med. 121(1980)(6) 939-949. Available: https://www.atsjournals.org/doi/10.1164/arrd.1980.121.6.939 (Accessed 12 January 2019). [11] H.L. Rieder. Intervention for Tuberculosis Control and Elimination. International Union of Tuberculosis and Lung Diseases, Paris, France, 2002.